The Letter and the Spirit of the Second Vatican Council: Does the Letter do Justice to the Spirit? - Tagle, Luis Antonio (Louvain studies, 2017)
This contribution is the transcript of the Opening Lecture given by Cardinal Tagle at the Leuven Encounters in Systematic Theology X 'The Letter and the Spirit: On the Forgotten Documents of Vatican II'. He argues that Vatican II was a ‘pastoral’ council that urges all members of the Church, and especially the ordained ministers, to become more ‘pastoral’ by highly valuing relationships and personal encounter